Plasma amino acid levels after carbon tetrachloride induced acute liver damage. A dose-response and time-response study in rats - Holecek, M; Skalská, H; Mráz, J (Amino acids, 1999)
The aims of the present study were to assess the changes of individual plasma amino acid levels in relation (1) to the severity of liver damage and (2) to the process of liver recovery. Acute liver injury was induced by an intragastric administration of CCl4 diluted in olive oil in doses of 2, 4 and/or 6 g of CCl4 per kg b.w. The control rats received olive oil only. Animals were sacrificed at 16, 24, 48 and 96 hours after treatment. The severity of liver injury was assessed by histological examination, by changes in ALT and AST in the blood plasma and by changes in liver weight. Statistical analysis was carried by ANOVA, p < 0.05 was considered significant. The Spearman rank correlation coefficient was used as a measure of the degree of linear relationship between variable and dose. In the period of the development of acute liver damage, i.e. at 16 and 24 hours after treatment, an increase in blood plasma amino acid levels and positive correlations with the dose of CCl4 were observed for most individual amino acids. The only exception was arginine which decreased in a dose dependent manner. At a phase of liver recovery, i.e. at 48 and 96 hours after CCl4 treatment, the concentrations of some individual amino acids decreased below the control values. The negative correlation with the dose of CCl4 occurred for taurine and isoleucine (at 48 hours) and taurine, threonine, valine, methionine, isoleucine and leucine (at 96 hours).
Keywords: Animals; otrava chloridem uhličitým; Alanine Transaminase; Aspartate Aminotransferases; vztah mezi dávkou a účinkem léčiva; Acute Disease; alanintransaminasa; Rats, Wistar; Organ Size; lékové postižení jater; Dose-Response Relationship, Drug; aspartátaminotransferasy; velikost orgánu; Male; krysa rodu Rattus; Carbon Tetrachloride Poisoning; Chemical and Drug Induced Liver Injury; akutní nemoc; Amino Acids; zvířata; mužské pohlaví; aminokyseliny; Rats; potkani Wistar